Interleukin-12 Inhibits Tumor Growth and Metastasis Promoted by Tumor-Associated Mesenchymal Stem Cells in Triple-Negative Breast Cancer - Babak Jahangiri; Zahra-Soheila Soheili; Elahe Asadollahi; Mehdi Shamsara; Vahid Shariati; Alireza Zomorodipour (Cell Journal)
Objective: The aim of this study was to understand the interactions between tumor-associated mesenchymal stemcells (TA-MSCs) and triple-negative breast cancer (TNBC) cells, which appear to be necessary for developing effectivetherapies.Materials and Methods: In this experimental study, MDA-MB-231 and 4T1 TNBC cells were co-cultured with bonemarrow-derived MSCs, and TA-MSCs conditioned media (CM) were collected. TA-MSC CM-treated TNBC cells weresubjected to migration and invasion assays. Epithelial-mesenchymal transition (EMT) marker expression was quantifiedby real-time polymerase chain reaction (RT-PCR). Cell proliferation was measured using trypan blue exclusiontechnique, while cell cycle distribution and apoptosis were assessed by flow cytometry. The effects of TA-MSCs ontumor volume, survival rate, and lung metastasis were evaluated by subcutaneous co-injection of MSCs with 4T1 cellsin the right flanks of BALB/c mice (n=5 per group). Intratumoral interleukin-12 (IL-12) immunotherapy was performedusing lentiviral particles as a rescue experiment. The TA-MSCs RNA-seq dataset (PRJEB27694) was analyzed todetect elevated metastasis-associated oncogenes, downloaded from the European Nucleotide Archive database. Forvalidation of the RNA-seq data analysis, the expression levels of candidate oncogenes were evaluated in TA-MSCs,TNBC cells, and tumor tissue using RT-PCR.Results: TA-MSCs enhanced migration, invasion, and EMT of TNBC cells in vitro without affecting cell proliferation orapoptosis. In vivo, TA-MSCs increased tumor growth and lung metastasis, while decreasing survival rates. IL-12 therapyelevated serum IL-12 and interferon-gamma (IFN-γ) expression, suppressed tumor volume and lung metastasis, andimproved overall survival in the TA-MSC group. RNA-seq data analysis identified upregulated oncogenes in TA-MSCs,among which MMP3, CXCL2, CXCL5, and ICAM1 were selected as the most relevant to metastasis. These genesshowed increased expression in TA-MSCs, TNBC cells, and tumor tissues.Conclusion: The findings of the present study revealed a complex interplay between TA-MSCs and TNBC cells thataffects tumor growth and metastasis. Preclinical results indicate that intratumoral IL-12 immunotherapy shows promisein overcoming TA-MSC-promoted tumor growth and metastasis.